2018
DOI: 10.14744/nci.2017.80958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trabeculectomy on the Ocular Higher Order Aberrations in Patients with Open Angle Glaucoma

Abstract: OBJECTIVE:The aim of this study was to evaluate the effect of trabeculectomy on ocular higher-order aberrations following surgery in a group of patients with open angle glaucoma.METHODS:In this prospective study, patients with primary open angle glaucoma underwent wavefront aberrometry before trabeculectomy with mitomycin-C. Coma-like, spherical-like, and total ocular higher-order aberrations were measured as root mean square values. The measurements were repeated 1 month and 3 months after the procedure.RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…There is no difference between our present study and Fard et al 11 ,study due to similar period of follow up after one month and close number of study group patients , however their study results were followed up after one and three months at which returned to baseline.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…There is no difference between our present study and Fard et al 11 ,study due to similar period of follow up after one month and close number of study group patients , however their study results were followed up after one and three months at which returned to baseline.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, Fardet al 11 , performed a prospective study of A total of 20 eyes from 20 patients. There was a significant decrease in intraocular pressure following surgery at 1 month and 3 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…During the first 3 months there are typically important changes in IOP, post-operative manipulations (e.g., injections, suture lysis) and important changes in bleb anatomy and configuration due to the scarring process. These changes as potential causes of the corneal aberrations have been reported in ocular or corneal aberrations, except spherical aberrations that were increased at 1–4 weeks after TLE, but they returned to control levels at 1–3 months [ 8 , 25 ]. The authors concluded that temporary ciliary body edema following TLE could change the thickness and position of the lens, and ACD induced the disturbance in ocular HOAs.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have revealed that ocular surgeries, such as intraocular lens implantation and cataract extraction [ 20 , 21 , 22 ] and scleral buckling [ 23 ], lead to a strong effect on corneal or ocular HOAs. Several studies have demonstrated changes in the refractive state or HOAs before and early post-TLE surgery [ 7 , 8 , 24 , 25 ]. In addition, some of these studies revealed that corneal or ocular HOAs were changed for 1 week–1 month after TLE, but they had returned to normal levels by 3 months [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Индуцированный послеоперационный роговичный астигматизм как осложняющий фактор так называемой проникающей офтальмохирургии был описан еще в начале XX века [3]. При этом, как правило, индуцированные изменения рефракции ассоциировали с операциями по поводу катаракты и режес антиглаукомными вмешательствами [4,5]. Между тем именно в последнем случае изменения рефракции более значимы, так как антиглаукомная хирургия направлена не на улучшение, а на сохранение имеющихся до вмешательства зрительных функций [6].…”
unclassified